Grewia polysaccharide as a pharmaceutical excipient in matrix tablets - Elijah I. Nep; Barbara R. Conway (Journal of Excipients and Food Chemicals, 2016)
Matrix-based tablets using different concentrations of grewia gum, and the model drug ibuprofen, were prepared using a wet granulation technique. Similar formulations were also prepared using HPMC, guar gum or ethyl cellulose as the polymer matrix. In addition to tablet properties, swelling and erosion of tablets and kinetics of drug release were also investigated. In vitro drug release studies, in phosphate buffer (pH 7.2) using USP type II apparatus, revealed that grewia gum at concentrations of 16%, 32% and 48% can sustain the release of ibuprofen tablets for up to 24 hours. Release profiles were similar to those tablets containing ethyl cellulose as the matrix former. Swelling and erosion of grewia gum matrices occurred simultaneously, and ibuprofen release was by anomalous diffusion in accordance with the Korsmeyer-Peppas model. There was evidence suggesting synergism between grewia gum and guar gum in sustaining the release of ibuprofen from tablets when used in the ratio 2:1. Grewia gum may therefore prove a useful excipient, when used on its own, or in combination with other polymers, to modify drug release.